Personal Role in the Mediation of Entrepreneurship Education on Interest in Entrepreneurship - Rismawati Rismawati; Nurhaedah Nurhaedah; Syed Norris (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2023)
This study has a purpose to analyze (1) To find out and explain the influence  of  Entrepreneurship  Education  on  Personal Management Students S1 at Stiesia Surabaya, (2) To find out and explain the Personal Influence on Interest in Entrepreneurship, (3) To  find  out  and  explain  the  influence  of  Entrepreneurship Education  on  Entrepreneurial  Interests  of  Management  S1 Students  at  Stiesia  Surabaya,  (4)  To  find  out  and  explain  the influence  of  Personal  roles  in  mediating  Entrepreneurship Education  on  Entrepreneurial  Interests  of  Undergraduate Management Students at Stiesia Surabaya. This research belongs to  the  type  of  research  in  the  category  of  explanatory  research, which  is  to  explain  a  relationship  between  variables  through hypothesis testing. The research sample amounted to 125 people. The  sample  in  this  study  using  the  census  method.  In  order  to analyze  the  data  the  author  uses  the  statistical  technique  Partial Least Square (PLS). The results of the research from the results of data  analysis  using  the  statistical  partial  least  square  (PLS) technique  which  can  be  seen  from  the  results  of  data  analysis which states that Entrepreneurship Education has a positive and significant influence on Personal, Personal can have a positive and significant  influence  on  Entrepreneurial  Interest.  positive  and significant  influence  on  Entrepreneurial  Interest  and Entrepreneurship  Education  indirectly  (through  the  Personality variable) significantly influence the Entrepreneurial Interest of S1 Management Students at Stiesia Surabaya.